(untitled) (Medical Forum Monthly, 2026)
Objective: To evaluate the outcome of intra-articular triamcinolone acetonide injection in patients with osteoarthritis of the knee. Study Design: Cross-sectional analytical studyPlace and Duration of Study: This study was conducted at the Department of Orthopedic surgery, National Hospital & Medical Center Lahore from 15th October 2025 till 15th of January 2026.Methods: This cross-sectional analytical study, including 85 patients with clinically and radiologically diagnosed knee osteoarthritis. All patients received intra-articular triamcinolone acetonide injection. Pain and functional outcomes were assessed using the Visual Analog Scale (VAS) and WOMAC score before and after treatment. Results: The mean age was 58.6 ± 9.4 years, with a female predominance (57.6%). The mean BMI was 28.9 ± 3.8 kg/m2. Significant improvement was observed in pain and function, with VAS scores decreasing from 7.8 ± 1.2 to3.9 ± 1.5 and total WOMAC scores improving from 63.3 ± 11.4 to 35.5 ± 10.2 (p <0.001). Overall, 72.9% of patients showed good to excellent improvement. Better outcomes were associated with younger age, lower BMI, shorter symptom duration, and less severe disease. Conclusion: Intra-articular triamcinolone acetonide injection provides significant short-term pain relief and functional improvement in knee osteoarthritis. It is an effective treatment option, particularly in patients with early- stage disease and fewer risk factors.